Diagnosis and treatment of autoimmune pancreatitis. Issue 5 (September 2018) - de Pretis, Nicolò; De Marchi, Giulia; Frulloni, Luca
Abstract : Purpose of review: Clinical management of autoimmune pancreatitis changed over the last years. The lack of high-quality studies, probably due to the relative rarity of the disease, has not fully clarified many diagnostic and therapeutic aspects. Aim of this review is to overview the literature from a clinical point of view, focusing on diagnostic and therapeutic approach to this complicated disease. Recent findings: They have been focused mainly on the risk of misdiagnosing a cancer. Many significant articles have been published on the treatment strategies of autoimmune pancreatitis, considering both induction and maintenance therapy. Summary: Diagnosis of autoimmune pancreatitis remains challenging, particularly in focal pancreatic involvement, despite recent advances on imaging modalities. Treatment is based on induction and maintenance phases. Steroid treatment remains the best option to induce remission. Maintenance therapy may be used to prevent disease relapses, and low-dose steroids, azathioprine or rituximab are the therapeutic options. However, it remains unclear which patient needs to be treated.